Learning the Meaning of Song Lyrics through the Elements of Ideational Metafunction: A Case on Systemic Functional Linguistics - Silalahi, Tiodora Fermiska; Purba, Ridwin; Manurung, Sri Maneni; Purba, Indra Pranata; Butar, Lukas Butar; Herman, Herman; Batubara, Junita; Tannuary, Arwin (Anglophile Journal, 2024)
The focus of the analysis is to identify and describe the various types of processes within the Experiential Function in the song's lyrics. Data source for this study is the song's lyrics, obtained from reliable sources such as the artist's official YouTube channel, Google, and various music applications. The lyrics are transcribed and used for identifying and categorizing the experiential processes found in the song. The data analysis method used in this research is qualitative analysis. It involves analyzing each clause in the lyrics and classifying them based on the Experiential Function's categories. The Experiential Function analysis helps to understand how the songwriter expresses their experiences, emotions, and perceptions through language in the song. This analysis of the Experiential Function in the song "A Year Ago" provides a comprehensive understanding of the songwriter's expressions of experiences and emotions, contributing to a deeper appreciation and interpretation of the song's lyrics. Keywords: Ideational Metafunction, Lyrics Songs, Systemic Functional Linguistics